Blockchain Development with Hyperledger : Build decentralized applications with Hyperledger Fabric and Composer /: Build decentralized applications with Hyperledger Fabric and Composer. (2019) - Baset, Salman A; Desrosiers, Luc; Gaur, Nitin; Novotný, Petr; O'Dowd, Anthony; Ramakrishna, Venkatraman; Sun, Weimin; Wu, Xun (Brian)
No abstract available